2021
DOI: 10.1021/acsomega.1c05458
|View full text |Cite
|
Sign up to set email alerts
|

Natural Boron and 10B-Enriched Hexagonal Boron Nitride for High-Sensitivity Self-Biased Metal–Semiconductor–Metal Neutron Detectors

Abstract: Metal–semiconductor–metal (MSM) detectors based on Ti/Au and Ni/Au interdigitated structures were fabricated using 2.5 micrometer thick hexagonal boron nitride (h-BN) layer with both natural and 10 B-enriched boron. Current–voltage ( I – V ) and current–time ( I – t ) curves of the fabricated detectors were recorded with ( I N ) and without ( I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…The strong interaction of boron nitride with neutron enables the fabrication of high-performance BN-based neutron detectors. 27,28 Our neutron damage experiments proved the strong interaction of PBN with neutron irradiation, and it has profound impact on the morphology, composition, and crystallinity. Figure S5 further compares the X-ray photoelectron spectroscopy (XPS) results of the HBN and PBN samples with and without various doses of neutron irradiation.…”
mentioning
confidence: 77%
See 1 more Smart Citation
“…The strong interaction of boron nitride with neutron enables the fabrication of high-performance BN-based neutron detectors. 27,28 Our neutron damage experiments proved the strong interaction of PBN with neutron irradiation, and it has profound impact on the morphology, composition, and crystallinity. Figure S5 further compares the X-ray photoelectron spectroscopy (XPS) results of the HBN and PBN samples with and without various doses of neutron irradiation.…”
mentioning
confidence: 77%
“…BN is a white, crystalline ceramic, commonly with a hexagonal crystal structure similar to that of graphite. Boron nitride has a wide range of applications, e.g ., lubricant, electrical insulators, thermal conductors, and deep ultraviolet (UV) emitter . Boron nitride is a well-known wide band gap semiconductor and has been successfully introduced for deep UV and neutron detection, benefiting from the decent charge transport properties (high sensitivity) and high resistivity (low noise level), making them ideal candidates for photodetection. For instance, Kaushik et al reported deep-ultraviolet photodetectors based on hexagonal boron nitride nanosheets and enhanced the device performance by localized surface plasmon resonance with Al nanoparticles . Liu and co-authors fabricated high-performance deep ultraviolet photodetectors based on few-layer hexagonal boron nitride and achieved ultra-high on/off ratio of >10 3 .…”
Section: Introductionmentioning
confidence: 99%
“…This includes boron and boron nitride among several others. Boron consists of two stable isotopes, namely 10 B and Boron-11 ( 11 B), among these two 10 B has a larger neutron cross section area [94,95] that is 3890 barns, hence it is quite often used in its enriched compound (boron carbide) form as control rods [96].…”
Section: Neutron Capturingmentioning
confidence: 99%
“…The average absorption length of natural h-BN for thermal neutrons is theoretically about 277 μm [136], and efficient neutron detection requires a sensitive region thick enough to ensure full collection of thermal neutrons. High melting point of h-BN and low vapor of boron make it difficult to obtain high quality and large size single crystal and epitaxial materials.…”
Section: The Ga 2 O 3 and Bn Detectormentioning
confidence: 99%
“…The data from PandX-4T set a stringent limit to the dark matter-nucleon spin-independent interactions, with the lowest excluded cross-section (90% CL) of 3.8 × 10 −47 cm 2 a WIMP of 40 GeV/c 2[236].There have been several experiments aimed at searching for 0 in a number of different candidate isotopes[238] such as136 Xe and82 Se, which has also been suggested as a promising isotope in the search for 0 . The PandaX-III employ high-pressure Xe TPC and EXO-200 employ liquid Xe TPC looking for 0 in the136 Xe. The N DEx experiment utilizes a high-pressure Se TPC searching 0 in the82 Se.…”
mentioning
confidence: 99%